Features of Chinese patients with sitosterolemia - Zhou, Zhizi; Su, Xueying; Cai, Yanna; Ting, Tzer Hwu; Zhang, Wen; Lin, Yunting; Xu, Aijing; Mao, Xiaojian; Zeng, Chunhua; Liu, Li; Li, Xiuzhen (BioMed Central, 2022)
Background: Sitosterolemia is a lipid disorder characterized by the accumulation of phytosterols in plasma and organs, caused by mutations in the ABCG5 and/or ABCG8 genes. The disease is frequently misdiagnosed and mistreated as familial hypercholesterolemia (FH). To gain a better understanding of the disease, the current status of diagnosis and treatment of Chinese patients with sitosterolemia was reviewed and summarized. Method: Literature search was performed. The clinical features and molecular characteristics of Chinese patients with sitosterolemia were analysed. Four children with sitosterolemia and the treatment experience were described. Results: Fifty-five patients with sitosterolemia have been reported in China. These patients were aged from 3 months to 67 years at diagnosis, and the median was 8 years of age. Several complications, such as xanthomas in 47 patients (85%), thrombocytopenia in 17 patients (31%), anemia in 14 patients (25%), and cardiovascular damage in 12 patients (22%), were observed. Thirty-nine patients (71%) exhibited mutations in the ABCG5 gene, 15 patients (27%) showed mutations in ABCG8, and variations in both genes occurred in one patient (2%). A patient with two clinically rare diseases, namely, sitosterolemia and glycogen storage disease type VI (GSD VI)), is reported here for the first time. The four reported patients were treated with low cholesterol and phytosterol-limited diet alone or combined with cholestyramine. Even though decreases were observed for total plasma cholesterol (TC) and low-density-lipoprotein cholesterol (LDL-C), and these levels were as low as normal in some patients, the levels of plant sterols remained above the normal range. However, TC, LDL-C and plant sterol levels remained at high levels in patients treated with a control diet control only. Conclusions: The analysis reveals that different from Caucasians carrying mainly variations in ABCG8, most Chinese patients have mutations in the ABCG5 gene, and Arg446Ter, Gln251Ter, anArg389His might be hot-spot mutations in Chinese patients. The current survey provides clinical data to enable the development of a standardized protocol for the diagnosis and treatment of sitosterolemia in China.